Analisis Sentimen Twitter terhadap Tren Penyebaran Informasi Pelaku Kejahatan Menggunakan Algoritma Naives Bayes - Awwaliyah Aliyah; Nailah Azzahra; Aliffia Isma Putri; Nur Aini Rakhmawati (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
In the rapidly developing digital era, social media such as Twitter has become part of everyday life and facilitates the rapid dissemination of information, including information about criminals. This research aims to analyze public sentiment towards information about criminals spread on Twitter using the Naive Bayes algorithm. This algorithm was chosen because of its simplicity and effectiveness in text classification. Data was collected through a crawling process from Twitter, followed by a preprocessing stage to remove noise. The research results show that public sentiment towards information about criminals on Twitter is divided into three categories: positive, neutral and negative. After classification, it was found that neutral sentiment increased significantly to 63.4%, while positive and negative sentiment decreased to 10.5% and 26.1%. These findings indicate that people tend to be more careful in reacting to sensitive information. This research provides important insights for related parties in managing information about criminals on social media and can be a reference for developing further policies and strategies.